2017
DOI: 10.1158/1055-9965.epi-17-0040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Natural History of Genital HPV Infection among Men by Country: Brazil, Mexico, and the United States

Abstract: Background Male genital HPV prevalence and incidence has been reported to vary by geographical location. Our objective was to assess the natural history of genital HPV by country among men with a median of 48 months of follow-up. Methods Men aged 18–70 years were recruited from US (n=1326), Mexico (n=1349), and Brazil (n=1410). Genital specimens were collected every six months and HPV genotyping identified 37 HPV genotypes. Prevalence of HPV was compared between the three countries using the Fisher’s exact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
3
30
2
Order By: Relevance
“…In less developed countries, cervix cancer is the second most common cancer (5) caused mostly by HPV-16 and -18 (6); however, cervical cancer is the 12 th most common cancer among Iranian female subjects (7). In male subjects, HPV-16 is the most frequent HPV genotype detected in penile cancer, and HPV-6 and -11 are often seen in genital warts (8). Although few studies have been carried out on HPV genotype distribution in Iranian male subjects, a recent study reported the 55.7% prevalence of HPV with HPV-6 as the most frequent genotype (9).…”
Section: Introductionmentioning
confidence: 99%
“…In less developed countries, cervix cancer is the second most common cancer (5) caused mostly by HPV-16 and -18 (6); however, cervical cancer is the 12 th most common cancer among Iranian female subjects (7). In male subjects, HPV-16 is the most frequent HPV genotype detected in penile cancer, and HPV-6 and -11 are often seen in genital warts (8). Although few studies have been carried out on HPV genotype distribution in Iranian male subjects, a recent study reported the 55.7% prevalence of HPV with HPV-6 as the most frequent genotype (9).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that β-HPV type-specific agreement was more common in the Mexican population as compared to Brazil and the US populations. In fact, among men from the HIM study, we also recently reported significant geographic differences in the natural history of α-HPV types 6 and 16 genital infection (Sudenga et al, 2017). Interestingly, we observed that β-HPV types for which strength of agreement for any two anatomical sites was moderate or substantial were not the most prevalent in the populations analyzed (Nunes et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…HPVs 16, 51, and 59 were the most commonly detected HR-HPV types, and HPV 84, 62 and 6 were the most prevalent LR-HPVs, although some regional differences were observed regarding the distribution of viral types. Furthermore, the prevalence and incidence of the predominant disease-causing genital HPVs infections in males (HPVs 16 and 6) were also significantly higher among men from Brazil than men from Mexico [63]. It is important to mention that solely discrete differences in the burden of genital HPV infection among MSM (men who have sex with men) and MSW (men who have sex with women) in all 3 countries analyzed were observed [57].…”
Section: Hpv Genital Infection and Associated Diseases: The Him Studymentioning
confidence: 99%